An annotated chromosome-level genome of a troglophilic spider (Pimoa clavata) - Yiming Zhang; Xiaoqing Zhang; Tongyao Jiang; Yejie Lin; Shuqiang Li (Scientific Data)
Abstract Climatic upheavals throughout Earth’s history have driven species to subterranean refugia, where stable microclimates buffer environmental extremes. The spider family Pimoidae, relict lineages sensitive to thermal fluctuations, exemplifies this climate-driven habitat transition. Here, we present the first chromosome-level genome of Pimoa clavata, a troglophilic spider endemic to Beijing’s mountainous caves. Combining PacBio HiFi and Hi-C sequencing, we assembled a 1.94 Gb genome with 29 scaffolds in chromosomes level, which were further subjected to comprehensive annotation. The well-annotated genome of this species provides foundational insights into the genomic basis of subterranean adaptation, offering critical resources for evolutionary genomics and conservation of climate-vulnerable cave species.